2007
DOI: 10.1007/s11064-007-9440-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hippocampal Cell Differentiation in the Subgranular Zone of the Dentate Gyrus in a Rat Model of Type II Diabetes

Abstract: It has recently been reported that diabetes mellitus is strongly associated with neurodegenerative and functional disorders of the central nervous system. In the present study, we investigated the changes in proliferating neurons in the dentate gyrus of type II diabetic rats using doublecortin (DCX), a marker of progenitors differentiating into neurons. At 4 weeks after birth, there were no differences in the blood glucose levels of Zucker diabetic fatty (ZDF) rats or Zucker lean control (ZLC) rats. DCX-immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 26 publications
6
42
0
Order By: Relevance
“…Also, several studies have reported reduction of neuronal density in dentate gyrus of animals with type 1 and 2 diabetes mellitus (Hwang et al, 2008;Kim et al, 2003;Li et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies have reported reduction of neuronal density in dentate gyrus of animals with type 1 and 2 diabetes mellitus (Hwang et al, 2008;Kim et al, 2003;Li et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The marker for neuronal proliferation, differentiation and migration, development, Ki67, doublecortin (DCX), NeuN were used for clarifying the neuronal proliferation, neurogenesis and development of hippocampus in this study. Especially, it has been recently reported that DCX is expressed in differentiated neurons (15), suggesting a role for DCX in neuronal plasticity, axonal outgrowth, or synaptogenesis (16,17). In this study, we used Ki67 to find a neuronal proliferation, DCX to find a neuronal differentiation and NeuN to find mature neuron in the subgranular zone of the DG.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of Leprfa gene and experimental design: Genotype of Lepr fa gene herein was determined with the strategy described in our previous study [16]. For effects of exercise on CR immunoreactivity at early and chronic stages, 20 male ZLC and ZDF rats in each were randomly divided into 4 groups (n=5 per group) as reported previously [17]: sedentary ZLC (Co-ZLC), sedentary ZDF (Co-ZDF), exercised ZLC (Ex-ZLC) and exercised ZDF (Ex-ZDF).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic T2DM leads to cognitive impairment [3,11,28,35], a reduction in brain hippocampal volume [12], dementia, and an increase in the risk for Alzheimer's Disease [39,47]. In addition, it has been reported that diabetes negatively affects hippocampal cell proliferation, differentiation, and neurogenesis [16,22,36]. Many studies have reported that exercise causes an increase in learning, cognitive function, and neurogenesis in the dentate gyrus (DG) [33,42,43].…”
mentioning
confidence: 99%